PEGylation of 6-amino-6-deoxy-curdlan for efficient in vivo siRNA delivery. (5th May 2016) - Altangerel, Altanzul; Cai, Jia; Liu, Lixia; Wu, Yinga; Baigude, Huricha; Han, Jingfen
Highlights: 6-Amino-6-deoxy-curdlan is PEGylated and characterized. PEGylated 6-amino-6-deoxy-curdlan shows high affinity to short interfering RNA. PEGylated 6-amino-6-deoxy-curdlan is biocompatible. Fluorescein labeled PEGylated 6-amino-6-deoxy-curdlan distributes in mouse liver. PEGylated 6-amino-6-deoxy-curdlan efficiently delivers siRNA to mouse liver. Abstract: RNA interference (RNAi) is an evolutionarily conserved gene-silencing phenomenon that shows great promise for developing new therapies. However, the development of small interfering RNA (siRNA)-based therapies need to establish efficient delivery system that silences target genes with siRNA doses that is clinically feasible in humans. Here we report synthesis and in vivo study of a novel PEGylated curdlan-based nanoparticle, designated as 6AC-100PEG, obtained by conjugation of mPEG 2000 to 6-amino-6-deoxy-curdlan. The complex of siRNA/6AC-100PEG showed homogenous nanoparticles with an average diameter of 200 nm. MTT assay indicated that 6AC-100PEG does not have apparent cytotoxicity. Systemic administration of a complex of siapoB/6AC-100PEG significantly reduced the level of apoB mRNA in mouse liver, indicating that 6AC-100PEG can efficiently deliver siRNA to mouse liver and induce RNAi. Administration of siRNA/6AC-100PEG to mouse did not elevate liver enzyme level in the serum, indicating that 6AC-100PEG nanoparticle is a promising in vivo siRNA delivery agent.